Electronic structure, chemical bonding features, and electron charge density of the double-cubane single crystal [Sb7S8 Br 2] (AlCl4)3 - Ali Hussain, Reshak, Prof. Dr.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Auluck, S.; Minofar, B.; Kityk, I. V. (American Institute of Physics, 2011)
Link to publisher's homepage at http://www.aip.org/